(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Technical Vocational Education and Training (TVET) institutions require an efficient system for managing trainer workloads, trainee progress, and training program information, but many continue to utilize manual or paper systems that result in disorganized records, limited monitoring capabilities, and delays in decision-making. Therefore, the purpose of this study was to design, develop, and evaluate a web-based training management system, SkillSync, to be implemented at Ramon Magsaysay Memorial Colleges, School of Technical Vocational Education and Training (RMMC-STVET). The research design was a combination of developmental and descriptive-evaluative research. SkillSync was developed through system development requiring data collection, testing, and piloting with administrators, trainers, and trainees using a survey, and the System Usability Scale (SUS) was utilized to evaluate the system. The data collected provided evidence that SkillSync is effective in supporting the management of training data and has improved the accessibility and organization of training data significantly. The SUS total score of 86.0 indicates an extremely usable system with a very high level of user satisfaction. Results also indicated that the users were highly accepting of the system by all stakeholders who were part of the evaluation process. In summary, SkillSync is a functional, user-friendly tool that can make a significant improvement in the efficiency of managing training and supporting decision-making for technical vocational education and training (TVET). SkillSync has demonstrated that web-based technology can enhance the administrative functionality of TVET institutions and promote the digital transformation of the administrative functions of TVET institutions.